The Relationship Between First-Trimester Aneuploidy Markers and Birth Weight - Soysal, Cenk; Sari, Hatice; Erten, Ozlem; Biyik, Ismail; Ince, Onur; Tasci, Yasemin; Keskin, Nadi (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: We aimed to determine the relationship between the first-trimester aneuploidy screeningma and the predicted weight at birth: Small for gestational age and large for gestational age. STUDY DESIGN: 594 low-risk pregnant women with a singleton pregnancy, who underwent first-trimester aneuploidy screening by measuring nuchal translucency, maternal serum free beta-human chorionic gonadotropin, and pregnancy-associated plasma protein-A were included in the study. Those weighing above the 3rd percentile and below the 10th percentile were defined as small for gestational age, and those over the 90th percentile were defined as large for gestational age. RESULTS: A total of 594 pregnant women were enrolled. The mean maternal age of the studied group was 28.8±5.5 years. Low maternal serum pregnancy-associated plasma protein-A levels and decreased nuchal translucency measurements were associated with the small for gestational age newborn (p<0.001 and p=0.001, respectively). There is a significant correlation with large for gestational age for newborns only with an increase in maternal serum pregnancy-associated plasma protein-A levels (p=0.001). beta-human chorionic gonadotropin levels were not associated with the birth weight (p=0.735). CONCLUSION: Maternal serum pregnancy-associated plasma protein-A levels, one of the markers in first-trimester aneuploidy screening, can be used in the prediction of small for gestational age and large for gestational age However, due to its low correlation, it is not a suitable screening test for clinical practice.